Factors influencing quality of processing in EMDR therapy - Ramallo-Machín, Alejandra; Gómez-Salas, Francisco J.; Burgos-Julián, Francisco; Santed-Germán, M. A.; Gonzalez-Vazquez, Ana Isabel (Frontiers in Psychology, 2024)
This study presents a preliminary analysis of a new instrument oriented at the analysis of processes in EMDR trauma therapy, the Processing Difficulties Scale (PDS). This scale includes 17 items described by experienced EMDR consultants and practitioners as indicative of problems during memory reprocessing.The proposed factorial solution based on four factors explains a total variance explained of 55% and an adequate goodness of fit, based on the proposed indices: RMSEA = 0.07; TLI = 0.91; CFI = 0.95. Table 1 shows the factorial loads for each of the items. The first factor includes 5 items (7, 8, 9, 10, 11), the second factor includes 6 items (13, 14, 25, 27, 28, 31), the third factor includes 3 items (3, 16, 22) and the fourth factor includes 3 items (19, 23, 24). Confirmatory analysis confirms the factorial solution proposed in the exploratory analysis factor and based on four factors with 17 items.1The analysis of internal consistency from Cronbach's alpha and the Omega index shows good internal consistency: Factor 1 (good processing; α = .92; ω = .94), Factor 2 (lack of generalization and/or absence of changes; α = .87; ω = .90), Factor 3 (poor emotional processing; α = .83; ω = .85) an Factor 4 (loss of dual attention; α = .82; ω = .83). In the case of the total scale, both coefficients exceeded .90, with an alpha of .92 and an Omega of .94. The convergent and discriminant validity criteria were estimated by calculating correlations, exploring the relationship between the factors resulting from the final result, the global severity index (GSI) of the SCL-90 and the level of improvement (NGS). These statistical analyses showed good levels of convergent and discriminant validity for all final factors.The PDS may offer a different perspective to analyze the controversy between clinicians and researchers about the need of a preparation phase in patients with complex early traumatization, dissociative symptoms and/or emotion dysregulation, and the different results in specific research around this topic.